Altered immunoexpression of e-cadherin and C-erbB2 in salivary gland adenoid cystic carcinoma: Correlation with the degree of histopathological malignancy - Mariam, Marry Siti (Padjadjaran Journal of Dentistry, 2009)
Adenoid Cystic Carcinoma (ACC) is a type of malignancy found in salivary gland, but its neoplasm prognosis is hard to predict. It grows slowly but spread continuously to its surrounding tissues and metastasizes hematogenously with a very high level of relapse. Histological, ACC of salivary gland is a combination of three types of growth phases (tubular, cribiform and solid), the solid type is > 30%, represented the worst prognosis. C-erbB2 proto-oncogene assumed as a prognosis symptom of salivary gland carcinoma, whilst the result of C-erbB2 expression in ACC salivary gland of was remained to be controversial. E-cadherin immunoexpression in ACC of breast gland used as the symptom of malignancy. Some experiments found that C- erbB2 oncogene product can be inducted the decrease of E-cadherin gene expression. Therefore, this experiment was conducted to find out the alteration of E-cadherin adhesion protein immunoexpression and C-erbB2 proto-oncogene in salivary gland ACC, in its correlation with the degree of its histopathological malignancy. The research design was a cross-sectional study at 51 block of paraffin which produced retrospectively by the patients with adenoid cystic carcinoma of salivary gland. All the samples of tumors were re-diagnosed to get the data of histopathological malignancy degree (as a modification of Szantos and Batsakis methods) with the smear of HE. Afterward, they got an immunohistochemistry, toward E-cadherin and C-erbB2. The result of the research showed that E-cadherin expression has negative correlation with the increase of histopathological malignancy degree. The low or non-existing of E-cadherin in salivary gland is related to high degree of histological malignancy (p< 0.01). Whilst the changed of E-erbB2 expression had significant correlation with the degree of histopatological malignancy (p < 0.03), but itâs correlation with the increase of histopathological malignancy was insignificant (p = 0.11). In summary, E-cadherin expression could be used as an indication of tumor to predict the prognosis malignancy of adenoid cystic adenoma of salivary gland. C-erbB2âs role in salivary gland ACC related to its biological acts.